The Development of Audit Quality Indicators - LITTLE, Harold Thompson; Lehkamp, Jenna M. (Archives of Business Research, 2018)
Over the years, there has been much debate regarding audit quality. The industry has struggled with how to define audit quality, as well as, how to identify the proper framework and indicators for assessing audit quality. Audit quality gained even more attention after corporate scandals, such as Enron (2001), WorldCom (2002), Tyco (2002), HealthSouth (2003), American Insurance Group (2005), Bernie Madoff (2008) and Lehman Brothers (2011). These scandals shattered the publics’ opinion of the accounting and auditing profession and caused investors to question the quality of the audits performed. To date, there is still “little agreement on how to define audit quality, let alone how to measure it” (Dickins et al. 2014, 1). This paper reviews the most recent academic articles published in the top journal during 1981 through 2017. Key words: audit quality indicators; audit quality; assurance; AQI